2003
DOI: 10.1007/s00418-003-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal inflammation on capsaicin-sensitive afferents in the ileum of Schistosoma mansoni -infected mice

Abstract: In the present study, the effect of intestinal schistosomiasis on the extrinsic sensory innervation of the murine ileum was investigated. Immunocytochemical techniques to localize calcitonin gene-related peptide (CGRP), substance P (SP), and vanilloid receptor 1 (VR1) were combined with retrograde tracing techniques and capsaicin treatment. Neurochemical characterization of extrinsic primary afferent neurons (EPANs) in normal and capsaicin-treated mice, revealed that CGRP and VR1, but not SP, were expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…51 CGRP has also been reported to exert chemotactive effect and promote mast cells recruitment. 62 In our study, CGRP blockade does not reverse the protective effect of exogenous PAR 2 activation in intestinal ischemia, suggesting rather a proinflammatory role of CGRP. 31 By contrast, in view of the increased damage score in SO rats pretreated with CGRP 8 -37 compared with saline SO rats, we cannot exclude a protective role of CGRP in mild inflammatory status, as induced by laparotomy and intestinal manipulation.…”
Section: Discussionmentioning
confidence: 77%
“…51 CGRP has also been reported to exert chemotactive effect and promote mast cells recruitment. 62 In our study, CGRP blockade does not reverse the protective effect of exogenous PAR 2 activation in intestinal ischemia, suggesting rather a proinflammatory role of CGRP. 31 By contrast, in view of the increased damage score in SO rats pretreated with CGRP 8 -37 compared with saline SO rats, we cannot exclude a protective role of CGRP in mild inflammatory status, as induced by laparotomy and intestinal manipulation.…”
Section: Discussionmentioning
confidence: 77%
“…Based on previous studies in the mouse by our group and others and the limited IR in perikarya, these fibers are presumed to originate extrinsically in the spinal and vagal ganglia (De Jonge et al 2003;Ward et al 2003;Matsumoto et al 2011). The intracellular staining by Gp-anti-TRPV1 hints at a splice variant because this splicing affects translocation to the membrane (Hellwig et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the effects of TRPV1 on GI functioning have mostly been linked to its expression in extrinsic nerve fibers. Regardless of GI region or species, TRPV1 is widely known to be expressed in afferent nerve fibers (Guo et al 1999;Yiangou et al 2001;Poonyachoti et al 2002;Anavi-Goffer and Coutts 2003;Chan et al 2003;De Jonge et al 2003;Ward et al 2003;Schicho et al 2004;Kadowaki et al 2004;Faussone-Pellegrini et al 2005;Matsumoto et al 2011). Some of these studies also reported an intrinsic expression of TRPV1 in the GI tract of several mammalian species (Akiba et al 2001;Kulkarni-Narla and Brown 2001;AnaviGoffer et al 2002;Poonyachoti et al 2002;Anavi-Goffer and Coutts 2003;Chan et al 2003;Faussone-Pellegrini et al 2005), as further corroborated by a physiological study in the mouse by Penuelas et al (2007).…”
mentioning
confidence: 84%
“…The specimens were immediately immersed in 4% paraformaldehyde in 0.1 M phosphate buffer (pH 7.0) at room temperature. After a 10-min fixation period, the DRG were processed for cryosectioning according to published methods (9). To assess the presence of TRPV1 in spinal neurons, cryostat sections were immunocytochemically stained with a rabbit antibody directed against TRPV1 (AB5370; CHEMICON International, Temecula, CA; diluted 1:400) and a Cy3-conjugated goat anti-rabbit IgG (Jackson Immunoresearch Laboratories, West Grove, PA; diluted 1:4,000).…”
Section: Methodsmentioning
confidence: 99%